1998
DOI: 10.1021/ac980244q
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry at Micropipet Electrodes

Abstract: The use of micropipet electrodes for quantitative voltammetric measurements of ion-transfer (IT) and electron-transfer (ET) reactions at the interface between two immiscible electrolyte solutions (ITIES) requires knowledge of geometry of the liquid interface. The shape of the meniscus formed at the pipet tip was studied in situ by video microscopy under controlled pressure. The shape of the interface can be changed from a complete sphere to a concave spherical cap by varying the pressure applied to the pipet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
162
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(167 citation statements)
references
References 29 publications
4
162
1
Order By: Relevance
“…has been reported by various researchers [18,25,31,32]. Nirmaier and Henze reported that the cell time constant for establishing the electrode potential at the electrode surface varies linearly with the electrode surface radius for disk-shaped electrodes.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…has been reported by various researchers [18,25,31,32]. Nirmaier and Henze reported that the cell time constant for establishing the electrode potential at the electrode surface varies linearly with the electrode surface radius for disk-shaped electrodes.…”
Section: Introductionmentioning
confidence: 88%
“…PSCA experiments by Yuan et al [18], Beattie et al [31] and Shao and Mirkin [32] reported that the lower time scale (or charging time) for carrying out potential step experiments at a microITIES is crucially restricted by the large resistance at the narrow microhole of polymer membranes or glass micropipettes used to form such microITIES. Comparison of the charging time of a water | 1,2-dichloroethane (DCE) microinterface with a metal | water microinterface of the same size showed that the charging time of the former was nearly three orders of magnitude greater than that of the latter [18].…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, the overwhelming majority of SECCM studies have employed aqueous electrolyte solutions. Therefore, after the pipette is pulled, the outer wall is usually silanized with dimethyldichlorosilane [Si(CH 3 ) 2 Cl 2 ], rendering it hydrophobic, which helps to confine the aqueous meniscus to the very end of the tip (57). Both barrels are then filled with an electrolyte solution and, if desired, a redox mediator of interest.…”
Section: Probesmentioning
confidence: 99%
“…To make the ion more oil soluble, complexation with large, usually neutral species, is performed. Besides the already mentioned analytical applications 32 many other determinations with facilitated transport were reported, of which only selected few can be mentioned 16,[41][42][43][44][45][46][47][48][49] .…”
Section: Introductionmentioning
confidence: 99%